Topological classification of the oriented cycles of linear mappings - Rybalkina, T.V.; Sergeichuk, V.V. (Український математичний журнал, 2014)
We consider oriented cycles of linear mappings over the fields of real and complex numbers. the problem of their classification to within the homeomorphisms of spaces is reduced to the problem of classification of linear operators to within the homeomorphisms of spaces studied by N. Kuiper and J. Robbin in 1973. Розглядаються орiєнтованi цикли лінійних відображень над полями дійсних та комплексних чисел. Задача їхньої класифiкацiї з точністю до гомеоморфізмів просторів зводиться до задачі класифікації лінійних операторів з точністю до гомеоморфізмів просторів, яку вивчали Н. Койпер та Дж. Роббін у 1973 році.